Understanding Carbon Storage in Volcanic Soils Under Selectively Logged Temperate Rainforests - Arancibia-Miranda, N; Arancibia-Miranda, N (Elsevier B.V., 2017)
A disturbance due to selective logging causes the release of carbon from forest soils. Here, we examine this effect under Nothofagus stands in Andisols of southern Chile (39°38′S, 72°02′W, > 4000 mm yr− 1). We postulate that soil carbon destabilization caused by forest management is counteracted by two contrasting carbon stabilization mechanisms linked to pedogenic processes: (1) the formation of allophane-imogolite-like materials (i.e., short-range ordered aluminosilicate particles with a specific Al/Si molar ratio, for example in the present study 3.8) and (2) formation of Al- and Fe-carbon complexes. The aim of this study was to compare the effects of selective logging on the organic carbon storage of forest Andisols. We estimated that carbon storage occurred in the uppermost 1 m of soils under evergreen (EGF) and secondary growth mixed deciduous forests (DMF). The selective dissolution method was used to estimate the mechanisms of soil carbon storage. The soil carbon storage under the unmanaged EGF did not differ significantly from that of the stands measured 10 or 50 years after selective logging. Likewise, the soil carbon storage under DMF was similar to that under stands measured 2, 6 or 50 years after selective logging. Overall, soil carbon storage was 24% lower under DMF than under EGF, which was attributed to the faster decomposition of organic matter produced by deciduous forests. The soil pH of the Ah-horizon was significantly lower (4.5–5.1) than that of the subsoil (5.5–6.0) due to the leaching of cations, leading to the development of less allophanic properties (i.e., an aluandic horizon). This effect increased the formation of organo-mineral complexes and reduced the content of allophane-imogolite-like precursors (e.g., non-crystalline Si and Al). As a result, an inverse relationship was found between metals (Al, Fe) complexed with carbon and the content of non-crystalline Si and Al, both of which were within single horizons and the entire soil profile in general. We conclude that disturbances caused by forest management did not alter carbon storage in these Andisols, which can be explained by (1) the potential mechanisms of carbon stabilization studied here and (2) humid climate, which protected the bare horizon from irreversible drying after the management of these ecosystems, thus preventing potential carbon loss. © 2017 Elsevier B.V.